Effectiveness of Education Program on High School Males Students' Knowledge about Smoking - shubib, hashim; Muhammad, Qahtan Qassem (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): The present study aims to evaluate the effectiveness of the educational program on high school mal students' knowledge about smoking. Methodology: A quasi-experimental design was carried out to in AL-Kut City for the period from 20th September 2022 to 24th November 2022. A non-probability (purposive sample) sample of (60) student was selected, (30) student for the study group and (30) students for the control group from high Schools for Males. The data was collected by using an constructed questionnaire based on t from constructed educational program for the purpose of the study by direct interview using. Data were analyzed by using (SPSS) package version (25) through the descriptive statistical data analysis of frequency, percentage, mean of score and standard deviation, and inferential statistical data analysis of the T-test and ANOVA.Results: The findings revealed that students’ knowledge about smoking for the study group before and after the application of the education program, at the pre-test the majority of the students had poor knowledge (83%), at post-test I and II, all of them had good knowledge (100%). While the control group, the majority of the students’ knowledge was fair at pre-test, post-test I and pos-test II (83%), (93%) and (80%) respectively, which confirmed that the education program has enforced a significant improvement on students’ knowledge about smoking.Conclusions: The study concluded that the education program had improved students’ knowledge about smoking and can induce an effect on them to decrease the use of tobacco as a bad habit.Recommendations: The study recommends for using the educational program of the current study as a reference for high school students to expand their awareness about this common phenomenon to contribute in reducing tobacco use as a bad habit among high school students.